The Effect of Education and Unemployment on Poverty in Jambi Province - Rohmah Choirur; Suratno; Kuswanto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
This study aimed to determine the effect of education and unemployment on poverty in Jambi Province. This study uses quantitative methods to analyze the impact of the average length of schooling, expected years of schooling, and the open unemployment rate on poverty in Jambi Province for the 2017-2019 period. The subjects of this study were residents of every district and city in Jambi Province. The type of data in this study is secondary data obtained and collected indirectly from the object under investigation. The things of this research are nine districts and two cities in Jambi province for the period 2017-2019 from the official portal of the Central Statistics Agency (BPS) Jambi Province. The data used are the average length of schooling (RLS), expected years of education (HLS), and the open unemployment rate (TPT), and the number of poor people in Jambi Province in the 2017-2019 period. The results of the study show that education and unemployment simultaneously affect poverty in Jambi Province